Pemberdayaan Perempuan Dalam Perwali Nomor 43 Tahun 2020 Tentang Pengarusutamaan Gender Di Kota Surabaya - Maharani Devi, Sefty; Sukristyanto, Agus; Roisul Basyar, Muhammad (Jurnal Administrasi Publik dan Bisnis, 2025)
As a form of gender-responsive transformation, the Surabaya City Government participates in the development process by formulating gender mainstreaming policies. To accelerate gender mainstreaming in development in Surabaya City, concrete actions are needed from the Surabaya City Government in planning, formulation, implementation, budgeting, monitoring, and evaluation of development policies, programs, and activities that are gender-responsive. The Surabaya City Government has issued regulations on gender mainstreaming as part of its efforts to establish a gender-responsive city through various programs that empower women. This situation has prompted research into how women are empowered through the issuance of Regulation Number 43 of 2020 on Gender Mainstreaming in the City of Surabaya. This was analyzed using Naila Kabeer's (1999) theory of women's empowerment, which encompasses three main dimensions: resources, agency, and achievements. The research findings indicate that women's empowerment through the policy of Regulation No. 43 of 2020 on Gender Mainstreaming in the City of Surabaya has been implemented through various programs and innovations, such as the Informal Women's School (SEKOPER) ‘Srikandi’, Women's Musrenbang, and the strengthening of Gender-Responsive Districts (KRG) and Women-Friendly and Child-Caring Neighborhoods (KRPPA). This study focuses solely on one program, namely the Informal Women's School (SEKOPER) ‘Srikandi’. This program serves as a learning platform for vulnerable women or single parents, aiming to strengthen the concept of motivation within the social environment. From a resource perspective, the Women's School Srikandi program has improved women's access to education and economic training. The agency dimension is reflected in increased women's participation in decision-making and policy-making. In terms of outcomes, there have been positive impacts, including increased income, self-confidence, and awareness of women's rights among program participants.